Successful Endoscopic Endonasal Repair of Nasal Meningoencephalocele in a 21-Day-Old Neonate. Issue 2 (June 2015) - Mohindra, Satyawati; Mohindra, Sandeep; Kumar Patro, Sourabha
Introduction: Indications of surgical intervention in congenital nasal meningoencephaloceles includes presence of cerebro spinal fluid rhinorrhea having a risk of causing meningitis, episodes of prior meningitis and bilateral nasal obstruction causing respiratory difficulty in these obligate nasal breathers. Many authors would like to wait till the patient attains the age of 2 to 3 years for repair of the defect due to surgical feasibility. However, early intervention prevents further episodes of meningitis in the future. We present the youngest patient of nasal meningoencephalocele successfully repaired via endoscopic approach. Case Report: A 21 days old neonate was referred to us with a nasal meningoencephalocele with active cerebrospinal fluid rhinorrhoea. Radiological investigation showed a cribriform plate defect on the right side. Repair was done by endoscopic route by multi-layered closure of the defect which was augmented with a mucoperichondrial flap from the septum. Patient was asymptomatic in the post-operative follow up period and did not have any episode of meningitis till date. Conclusion: Early repair by transnasal endoscopic route is a feasible surgical option for congenital anterior skull base defects with meningoencephaloceles to prevent further episodes of meningitis. This is feasible even in the neonatal period due to improved technique and instrumentation now available for endoscopic nasal surgeries.